A General Characterization of Optimal Income Tax Enforcement - Chander, Parkash; Wilde, Louis L. (Review of Economic Studies, 1998)
This paper develops a general approach to characterizing optimal income tax and enforcement schemes. Our analysis clarifies the nature of the interplay between tax rates, audit probabilities and penalties for misreporting. In particular, it is shown that for a variety of objective functions for the principal the optimal tax schedule is in general concave (at least weakly) and monotonic; the marginal tax rates determine the audit probabilities; and less harsh penalties lead to higher enforcement costs. Our results imply that there exists a tradeoff between equity and efficiency considerations in the enforcement context which is similar to that in the moral hazard context for tax policy.